Actuators: Smarter Actuator Design with Complementary and Synergetic Functions (Adv. Mater. 30/2015). (August 2015) - Khaldi, Alexandre; Plesse, Cedric; Vidal, Frederic; Smoukov, Stoyan K.
<x xml:space="preserve">Abstract</x> A general combinatorial synthesis overcomes tradeoffs in designs for multi‐functionality. As described by S. K. Smoukov and co‐workers on page 4418, intertwining the synthesis of three already‐optimized single‐function materials into a single network—one color for each phase—generates thousands of triple functionalities. Linear artificial muscles and synergistic effects are demonstrated, and synthesis approaches outlined, with an outlook to replace whole devices with multifunctional materials. Image credit: Stoyan Smoukov, Jeff Hall, and Kevin Young.